A METHODOLOGY FOR ANALYSIS OF MANUFACTURING OPERATIONS DUE TO COMPLEXITY - Kamrani, Ali (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
Variability in products is driven by the customer and pushes the manufacturer to offer product variants by mass customization. Companies that offer product variety while maintaining competitive cost and quality will gain a competitive edge over other companies in today’s market. As auto industries adapt to mass customization strategy, they would require the ability to conduct early design, development and manufacturing trade-offs among competing objectives. An analytical approach is then required to manage the complexity and the risk associated with this environment. This article will present a set of simulation-based methodologies for measuring complexity. The developed methodologies will assist designers in analyzing and mitigating the risks associated with product variety and its impact on manufacturing.